2014
DOI: 10.1021/es504074z
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Arsenic Species in Unicellular Algae to the Cycling of Arsenic in Marine Ecosystems

Abstract: This review investigates the arsenic species produced by and found in marine unicellular algae to determine if unicellular algae contribute to the formation of arsenobetaine (AB) in higher marine organisms. A wide variety of arsenic species have been found in marine unicellular algae including inorganic species (mainly arsenate--As(V)), methylated species (mainly dimethylarsenate (DMA)), arsenoribosides (glycerol, phosphate, and sulfate) and metabolites (dimethylarsenoethanol (DMAE)). Subtle differences in ars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 144 publications
1
37
0
Order By: Relevance
“…Many studies showed that As(V) was the major arsenic species accounting for up to 99 % of the total As in cystolic fractions of microalgae cells (Duncan et al 2015;Goessler et al 1997;Levy et al 2005;Ohki et al 1999;Wang et al 2013b). Moreover, the As(III) oxidation of most microalgae occurs either in the periplasm or near the outer membrane, which should be regarded as a kind of survival mechanism over the long term evolution (Zhang et al 2014).…”
Section: As(iii) Oxidationmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies showed that As(V) was the major arsenic species accounting for up to 99 % of the total As in cystolic fractions of microalgae cells (Duncan et al 2015;Goessler et al 1997;Levy et al 2005;Ohki et al 1999;Wang et al 2013b). Moreover, the As(III) oxidation of most microalgae occurs either in the periplasm or near the outer membrane, which should be regarded as a kind of survival mechanism over the long term evolution (Zhang et al 2014).…”
Section: As(iii) Oxidationmentioning
confidence: 99%
“…Arsenolipids could be degraded to some toxic arsenic species (Meyer et al 2014;Taleshi et al 2014), so further investigation should be conducted on the possible toxic properties of these lipids and their influence on human health. Moreover, further research on the formation of arsenolipid species in microalgae is essential to understand the role of these organoarsenic compounds in As cycling (Duncan et al 2015). …”
Section: Formation Of Arsenolipidsmentioning
confidence: 99%
See 3 more Smart Citations